Vibrotactile feedback as a countermeasure for spatial disorientation - Vimal, Vivekanand Pandey; Panic, Alexander Sacha; Lackner, James R.; DiZio, Paul (Frontiers in Physiology, 2023)
Spaceflight can make astronauts susceptible to spatial disorientation which is one of the leading causes of fatal aircraft accidents. In our experiment, blindfolded participants used a joystick to balance themselves while inside a multi-axis rotation device in either the vertical or horizontal roll plane. On Day 1, in the vertical roll plane (Earth analog condition) participants could use gravitational cues and therefore had a good sense of their orientation. On Day 2, in the horizontal roll plane (spaceflight analog condition) participants could not use gravitational cues and rapidly became disoriented and showed minimal learning and poor performance. One potential countermeasure for spatial disorientation is vibrotactile feedback that conveys body orientation provided by small vibrating devices applied to the skin. Orientation-dependent vibrotactile feedback provided to one group on enhanced performance in the spaceflight condition but the participants reported a conflict between the accurate vibrotactile cues and their erroneous perception of their orientation. Specialized vibrotactile training on Day 1 provided to another group resulted in significantly better learning and performance in the spaceflight analog task with vibrotactile cueing. In this training, participants in the Earth analog condition on Day 1 were required to disengage from the task of aligning with the gravitational vertical encoded by natural vestibular/somatosensory afference and had to align with randomized non-vertical directions of balance signaled by vibrotactile feedback. At the end of Day 2, we deactivated the vibrotactile feedback after both vibration-cued groups had practiced with it in the spaceflight analog condition. They performed as well as the group who did not have any vibrotactile feedback. We conclude that after appropriate training, vibrotactile orientation feedback augments dynamic spatial orientation and does not lead to any negative dependence.